2007
DOI: 10.1016/j.ejcts.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of local recurrence following segmentectomy of stage IA non-small cell lung cancer is influenced by segment localisation and width of resection margins — implications for patient selection for segmentectomy☆

Abstract: The frequency of local recurrence following segmentectomy might be influenced by segment localisation and width of resection margins. Segmentectomy within the S1-3 region should be avoided whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
3
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 23 publications
1
86
3
8
Order By: Relevance
“…The 5-yr survival rates of their pT1N0M0 counterparts were 87.1% for extended segmentectomy and 87.8% for lobectomy (p50.8008). WARREN et al [25], KOIKE et al [28], WATANABE et al [32] and SIENEL et al [42] reported similar results in this selective group of patients with small T1 tumours.…”
Section: Tumour Sizesupporting
confidence: 70%
See 3 more Smart Citations
“…The 5-yr survival rates of their pT1N0M0 counterparts were 87.1% for extended segmentectomy and 87.8% for lobectomy (p50.8008). WARREN et al [25], KOIKE et al [28], WATANABE et al [32] and SIENEL et al [42] reported similar results in this selective group of patients with small T1 tumours.…”
Section: Tumour Sizesupporting
confidence: 70%
“…Finally, in the series of SIENEL et al [42], the cancer-related 5-yr survival rate for 150 patients who had undergone lobectomy was 83%, which was significantly higher than the 67% found in 47 patients who had undergone segmentectomy. However, again, when patients with tumours of f2 cm in diameter were considered, survival differences were not statistically significant.…”
Section: Survival and Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a large retrospective study (SEER) showed that lobectomy and segmentectomy resulted in similar survival among patients with small (,1 cm) tumours [62]. In a retrospective series, SIENEL et al [63] reported that local relapse after segmentectomy was more common in the S1-S3 region, especially when the resection margin was ,1 cm.…”
Section: Surgery For Early Stage Lung Cancer (Stage I and Ii)mentioning
confidence: 99%